Metafora sebagai Kekuatan Retorik dalam Editorial Media Massa - Mulharnetti Syas; Udi Rusadi (Jurnal Studi Komunikasi dan Media, 2021)
Editorial as a space of opinion for the media trying to influence its readers both through the structure of editorial anatomy and the use of language. One aspect of language is the use of metaphors. This article reports the results of research about how the rhetorical power of metaphors in the structure of editorial anatomy. The concepts and theories used are about metaphors as thoughts, editorial structures, and persuasive acts of rhetoric, namely: logos, ethos, and pathos. The method used to find the rhetorical meaning of the metaphor is the Metaphor Identification Procedure (MIP) that was presented by the Pragglejaz. The editorial studied is the editorial of the Republika Newspaper and Media Indonesia Newspaper. The results of the study showed that there are two major issues, namely the issue of a new cabinet and the issue of corruption. Metaphors are used in the anatomy of editorial attention, conviction, and direction, but they are not comprehensive. Metaphors become rhetorical powers as part of logos and phatos. The metaphors used in the new cabinet issue give warnings and demands to the elected president about the cabinet being drafted. The metaphors used in the issue of corruption build a picture and thought that the existing parliament does not have legitimacy as people's representatives. Theoretically, this research finds a double metaphorical rhetoric with an editorial anatomical structure that reinforces the persuasive dimensions of rhetoric on the elements of logos and phatos.Keywords: Editorial, Media, Metaphor, Rhetoric, StructureEditorial sebagai ruang opini bagi media berusaha untuk memengaruhi pembacanya, baik melalui struktur anatomi editorial, maupun penggunaan bahasa. Salah satu aspek bahasa adalah penggunaan metafora. Artikel ini melaporkan hasil penelitian tentang bagaimana  kekuatan retorik metafora dalam struktur anatomi editorial. Konsep dan teori yang digunakan ialah tentang metafora sebagai pemikiran, struktur editorial, dan tindakan persuasif retorika, yaitu:  logos, ethos dan pathos. Metode yang digunakan untuk menemukan makna retorik metafora ialah Metaphor Identification Procedure (MIP) yang dikemukakan Pragglejaz Group.  Editorial yang diteliti ialah editorial Suratkabar Republika dan Media Indonesia. Hasil penelitian menunjukkan, terdapat dua isu besar yang mengunakan metafora, yaitu isu kabinet baru  dan isu  korupsi. Metafora digunakan pada anatomi editorial attention, conviction, dan direction, tetapi tidak menyeluruh. Metafora menjadi kekuatan retorik sebagai bagian dari  logos dan phatos. Metafora yang digunakan dalam isu kabinet baru memberikan peringatan dan tuntutan pada presiden terpilih tentang kabinet yang disusun. Metafora yang digunakan dalam isu korupsi membangun gambaran dan pemikiran bahwa parlemen yang ada tidak memiliki legitimasi sebagai wakil rakyat. Secara teoritis,  penelitian ini menemukan retorika ganda (double rehoric)  metafora dengan struktur anatomi editorial yang memperkuat dimensi persuasif  reorika pada unsur logos dan phatos. Kata Kunci:  Editorial, Media, Metafora; Retorika, Struktur